UMPSA lecturers take action to raise awareness about the harmful effects of excessive sugar consumption among primary school students - Nor Adila, Mhd Omar (UMPSA, 2024)
KUANTAN, 15 August 2024 – A total of 175 primary school students from the Kuantan area participated in the Empowering Sugar Awareness: Sweet Kids, Healthy Lives Programme held at Sekolah Kebangsaan Pelindung, Kuantan, recently.